Kajian Kebijakan Pengampunan Pajak dengan Pendekatan Eksperimental - Kurniawan, Benny Robby; Juanda, Bambang; Bakhtiar, Toni (Jurnal Ekonomi dan Pembangunan Indonesia, 2019)
This research was conducted because the uncertainty in the tax amnesty policy. The purpose of this research is to analyze the effect of taxpayer’s expectation of future tax amnesty, tariff period system, tax penalty and audit towards tax compliance in tax amnesty policy, using experimental economics. The result shows that, a tax amnesty followed by strict audit and tax penalties will rise tax compliance. Tax amnesty policy is best applied once in a lifetime, because the expectation of the taxpayers towards future tax amnesty will result in lowering the compliance. Taxpayers prefer the lowest rate on tariff period.